Corporate Governance and the Sustainable Development (European Journal of Marketing and Economics, 2026)
Nowadays the issues of sustainable development are everywhere around us. Everybody talks about sustainability in all aspects of our life. It is becoming also part of the agenda of the business world not only for the small and medium size companies, but also for the big corporations. Gradually environmental and social issues begin to pose new topics in the agenda for board meetings of the big corporations. The corporate governance begins to pay more and more attention not only to the return rate of the investments but also to the footprint that the company has on the society. In this framework we decided to examine the relationship and interconnectivity between corporate governance and sustainable development. The research that backed this paper encompasses literature survey and analysis, on one hand and empirical research on another. This paper present some of the results from our survey showing the changes that occur in the corporate governance and the position of the managing boards of directors due to the sustainable development policy applied worldwide.
Keywords: sustainable development, corporate governance, corporate social responsibility, environment, governance